THE IMPACT OF PERTAMINA'S FUEL PRICE INCREASE ON COMPETITORS' COMPETITION STRATEGIES AND MARKET POSITIONS IN THE ENERGY INDUSTRY - Roydawaty Bunga (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
Private companies selling fuel at higher prices than Pertamina may face lower competitive pressure, as the price gap with Pertamina's products narrows. The objective of this research is to determine the impact of Pertamina's fuel price increase on the competitive strategies implemented by competitors in the energy industry, the changes in market positions of competitors after the price increase, and the challenges faced by energy companies in responding to this change. This study employs a qualitative descriptive method. The findings indicate that energy companies must continuously innovate and adapt to remain competitive in an economically dynamic environment. With the right strategies, competitors can maintain their market position and provide more sustainable energy solutions for society.